Impact of food allergy on food insecurity and health literacy in a tertiary care pediatric allergy population. Issue 3 (1st March 2019) - Dilley, Meredith A.; Rettiganti, Mallikarjuna; Christie, Lynn; O'Brien, Erin; Patterson, Megan; Weeks, Connelly; Aronson, Julia; Scurlock, Amy M.; Perry, Tamara T.; Pesek, Robbie D.; Bell, Matthew C.; Kennedy, Joshua L.; et al.
Abstract: Background: Food insecurity (FI), limited availability of or access to nutritional foods, is linked to poor child/caregiver health. We examined FI in food‐allergic and non‐food‐allergic children to determine whether dietary limitations associated with food allergy increases risk of FI. Methods: Food‐allergic and non‐food‐allergic children (1‐17 years) were recruited from Arkansas Children's Hospital allergy/asthma clinics. The USDA Food Security Survey, the Newest Vital Sign Health Literacy (HL) questionnaire, and the Food Allergy Impact Scale QOL survey were administered. Logistic regression and analysis of covariance models were utilized for data analysis. Results: Subjects (n = 650) included 325 food‐allergic and 325 non‐food‐allergic children. Overall rate of FI was 21.5% (food allergic 22.2% and non‐food allergic 20.9%) with no significant difference in the prevalence of FI between groups (OR = 1.30; 95% CI 0.86‐1.96; P = 0.21). FI was increased in households of children with both milk and egg allergy when compared to those without food allergy and those with single food allergy (OR = 2.5; 95% CI 1.4‐4.6; P = 0.003). Mean HL rates were higher in the food‐secure vs food‐insecure groups (mean diff = 0.31; 95% CI 0.03‐0.59; P = 0.03). Among food‐allergic children, QOL was better in the food‐secure vs food‐insecure group (mean diff = 0.61; 95% CI 0.002‐1.23; P = 0.049). Conclusion: Food allergy to milk and egg was associated with increased risk of household FI. Food‐insecure participants had lower HL than their food‐secure counterparts. Further work is needed to define risks associated with FI among food‐allergic children to improve screening and management strategies.